Identifying a lotus motif transformation on the Melaka traditional mosque’s roof crown in 1720-1950 / Raziq Abdul Samat … [et al.] - Abdul Samat, Raziq; Shaari, Shafirah; Madon, Dona Lowii; Meor Hamzah, Meor Hasmadi (2017)
Melaka have developed over 500 years of trade and cultural exchanged between East and West in the Straits of Malacca and had been recognized as a World Heritage by the UNESCO in 2008. Besides trading exchange, some of merchant brought an influence of religion, culture and also an art from their country to the Melaka. The process of assimilation of influence can be seen in cultures and buildings of Melaka. For example traditional mosques in Melaka have a different style of architecture compared to the other state mosques in Malaysia. It has a combination of influences from Sumatra and Chinese. There are some of motifs and pattern represent influence can be seen on the mosques. For this research paper, lotus motif from the roof crown also known as buton and mahkota atap of Melaka traditional mosques will become as a subject to study on the stylization permutation based on year. There are 20 traditional mosques were build in 1720-1950 will be selected and which is maintain the roof crown without replacing by doom. Objectively, this research paper is about to study the influences of Lotus motif and the relation of lotus motif with Malay and Islam perception. Visual research and content analysis method will use to gathering the data. Findings showed each of lotus motif have different style based on era which lotus motif in 17th era have a realistic and complexity compared than lotus motifs in 19th era which is more simplicity and stylization.